Gene Regulation and Functional Alterations Induced by Kaposi's Sarcoma-Associated Herpesvirus-Encoded ORFK13/vFLIP in Endothelial Cells - Sakakibara, Shuhei (American Society for Microbiology (ASM), 2009)
Kaposi's sarcoma (KS) is an angioproliferative inflammatory disorder induced by endothelial cell infection with the KS-associated herpesvirus (KSHV). ORFK13/vFLIP, one of the KSHV genes expressed in KS, encodes a 188-amino-acid protein which binds to the Iκb kinase (IKK) complex to activate NF-κB. We examined ORFK13/vFLIP contribution to KS phenotype and potential for therapeutic targeting. Retroviral transduction of ORFK13/vFLIP into primary human endothelial cells induces the spindle morphology distinctive of KS cells and promotes the formation of abnormal vascular networks typical of KS vasculature; upregulates the expression of proinflammatory cytokines, chemokines, and interferon-responsive genes; and stimulates the adhesion of inflammatory cells characteristic of KS lesions. Thymidine phosphorylase, a cellular enzyme markedly induced by ORFK13/vFLIP, can metabolize the prodrug 5-fluoro-5-deoxyuridine (5-dFUrd) to 5-fluouridine (5-FU), a potent thymidine synthase inhibitor, which blocks DNA and RNA synthesis. When tested for cytotoxicity, 5-dFUrd (0.1 to 1 μM) selectively killed ORFK13/vFLIP-expressing endothelial cells while sparing control cells. These results demonstrate that ORFK13/vFLIP directly and indirectly contributes to the inflammatory and vascular phenotype of KS and identify 5-dFUrd as a potential new drug that targets KSHV latency for the treatment of KS and other KSHV-associated malignancies.